2020
DOI: 10.1089/cap.2019.0124
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fish Oil Monotherapy on Depression and Prefrontal Neurochemistry in Adolescents at High Risk for Bipolar I Disorder: A 12-Week Placebo-Controlled Proton Magnetic Resonance Spectroscopy Trial

Abstract: Objectives: To evaluate the clinical and neurochemical effects of 12-week fish oil, a source of omega-3 polyunsaturated fatty acids (n-3 PUFAs), in depressed adolescents with a family history of bipolar I disorder. Methods: Adolescents with a current Diagnostic and Statistical Manual of Mental Disorders, 4th edition, Text Revision diagnosis of Major Depressive Disorder or Depressive Disorder not otherwise specified, a Childhood Depression Rating Scale-Revised (CDRS-R) Version raw score of ‡40, and at least one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 87 publications
1
19
0
Order By: Relevance
“…Another intervention trial in 60 depressed adolescents saw significant improvement, however [ 88 ]. Similar, but less pronounced, results were seen in another trial with 56 participants [ 89 ]. These positive trials question the overall neutral result of an earlier meta-analysis of four trials in a total of 153 participants [ 90 ].…”
Section: Children and Adolescentssupporting
confidence: 82%
“…Another intervention trial in 60 depressed adolescents saw significant improvement, however [ 88 ]. Similar, but less pronounced, results were seen in another trial with 56 participants [ 89 ]. These positive trials question the overall neutral result of an earlier meta-analysis of four trials in a total of 153 participants [ 90 ].…”
Section: Children and Adolescentssupporting
confidence: 82%
“…For example, a preliminary resting‐state MRI study found that feeding a diet enriched with saturated fatty acids, but not a diet enriched with monounsaturated fatty acids, for 12 weeks decreased hippocampal and inferior parietal cortex activity in healthy human subjects 72 . Although supplementation with olive oil did not significantly alter any erythrocyte fatty acid, including saturated and monosaturated fatty acids, 50 the direction of the changes in EPA+DHA and the AA/(EPA+DHA) ratio were opposite to those observed in the FO group. The present findings, therefore, provide additional evidence that dietary enrichment with saturated and monounsaturated fatty acids may significantly alter emotional‐generated corticolimbic functional connectivity, and that the pattern of change is opposite to that produced by FO supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Efficacy and safety results from this trial have been reported previously. 50 This study was approved by the Institutional Review Board of University of Cincinnati and was registered at clinicaltrials.gov with identifier NCT00917501. The data that support the findings of this study are available from the corresponding author upon reasonable request.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations